Performance Management Practices and Employee Performance in Local Governments: A Case Study of Tororo District Local Government - Ofwono Stanslaus Toto (Uganda Christian University, 2024)
The main objective of the research study was to examine the effect of performance management practices on employee performance in Tororo District Local Government. The specific objectives were to establish how performance standards affect employees’ performance, to determine the effect of performance measurement on employees’ performance, and to assess the impact of result dissemination on employees’ performance. Utilizing a cross-sectional study design, the research focused on a population of 67 and a sample size of 57, determined using Slovin's formula. The study findings revealed that performance standards had a significant positive effect on employee performance, with a regression coefficient of 0.75. Performance measurement also had a notable impact, with a coefficient of 0.68. Additionally, result dissemination positively influenced employee performance, with a coefficient of 0.62. The study concluded that effective performance management practices significantly enhance employee performance. It also concluded that consistent and transparent performance measurement and result dissemination are crucial for improving performance. The study recommended implementing robust performance standards and measurement systems, as well as ensuring transparent result dissemination to further enhance employee performance. It further recommended regular training and feedback mechanisms to support continuous improvement in performance management practices.